PENGELOLAAN BIAYA MODAL KERJA PENDIDIKAN: ANALISIS PERENCANAAN, PELAKSANAAN, DAN EVALUASI BELANJA MODAL - Rici Vidiono Puperta Agus; Hamdi Abdul Karim (PT. Hasba Edukasi Mandiri, 2026)
This research aims to comprehensively analyze the complete management cycle of educational capital expenditure, specifically encompassing the critical stages of strategic planning, public procurement, accounting administration, and long-term asset evaluation. Utilizing a critical literature review and public policy analysis design, this study meticulously examines the prevailing regulatory frameworks governing state finances. Data were primarily obtained through a systematic review mechanism, extracting qualitative information from national fiscal regulations, government procurement guidelines, and recent empirical studies on school financial management sourced from accredited academic databases to identify systemic bottlenecks. The results indicate that capital expenditure management in educational institutions is frequently hindered by myopic, non-data-driven planning mechanisms, severe bureaucratic delays, regional material inflation, and weak internal control systems that remain highly susceptible to budget misappropriation. The discussion highlights that these administrative pathologies significantly reduce the optimal utility rate of physical assets, thereby limiting their intended positive impact on the learning ecosystem, student motivation, and overall pedagogical effectiveness. The novelty of this research lies in its integrated strategy formulation, proposing the mandatory digitalization of the entire procurement lifecycle using centralized government platforms, alongside the strict implementation of risk-based preventive maintenance scheduling. These findings carry critical implications for the educational sector by offering a highly actionable, strategic blueprint for principals and policymakers to achieve total transparency and optimize the value for money in school infrastructure investments, effectively serving as a robust foundational reference for conducting related empirical investigations in the future.